Pemberdayaan Usaha Kecil Manisan Terong Ungu Di Desa Warnasari Kecamatan Pangalengan Kabupaten Bandung - Siti Patimah (Universitas Muhammadiyah Surakarta, 2021)
Candied Eggplant is a food processed product produced in Desa Warnasari, Kecamatan Pangalengan ,Kabupaten Bandung. This candy is unique because it is made from purple eggplant which is usually used as a complementary vegetable to eat. However, currently purple eggplant can be used as processed snacks, especially sweets. The problems faced by business actors are related to still experiencing problems in marketing products. The production process in terms of packaging is still very simple. In addition, the determination of the selling price is carried out in an estimate so that partners often experience losses.The method of implementation is in the form of training and technical guidance. The training is delivered by giving lectures and understanding related to marketing, production and finance. Bintek that is done is by direct practice given to partners.The results of the community service that have been carried out are in the form of training and information technology related to marketing, production and finance. Marketing that has been carried out so far is still offline so partners are trying to do it online even though only with WA and additions so that products can be recognized by using labels, then production by means of packaging that can use a smaller space and size. As well as the provision of production tools. Then provide an understanding of determining the cost of production and profit and loss. The output produced by partners understands related to the use of WA, the production process and finance